2009
DOI: 10.3164/jcbn.08-257
|View full text |Cite
|
Sign up to set email alerts
|

A Rice Bran Oil Diet Improves Lipid Abnormalities and Suppress Hyperinsulinemic Responses in Rats with Streptozotocin/Nicotinamide-Induced Type 2 Diabetes

Abstract: The aim of this study was to determine the effects of rice bran oil (RBO) on lipid metabolism and insulin resistance in rats with streptozotocin/nicotinamide-induced type 2 diabetes mellitus (T2DM). Rats were divided into two groups: the control group (15% soybean oil, contains 0 g γ-oryzanol and 0 g γ-tocotrienol/150 g oil for 5 weeks) and the RBO group (15% RBO, contains 5.25 g γ-oryzanol and 0.9 g γ-tocotrienol/150 g oil for 5 weeks). Compared with the control group, the RBO group had a lower plasma noneste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 48 publications
4
45
0
Order By: Relevance
“…This finding is in agreement with previous studies that there are no positive reduction of plasma and hepatic cholesterol concentrations [21]- [24]. Chou et al [25] observed that the rice bran oil group (0.9 g γ-tocotrienol and 5.25 g γ-oryzanol/kg diet) did not lower plasma total cholesterol, triglyceride, and LDL cholesterol and hepatic triglyceride levels compared with the control group.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in agreement with previous studies that there are no positive reduction of plasma and hepatic cholesterol concentrations [21]- [24]. Chou et al [25] observed that the rice bran oil group (0.9 g γ-tocotrienol and 5.25 g γ-oryzanol/kg diet) did not lower plasma total cholesterol, triglyceride, and LDL cholesterol and hepatic triglyceride levels compared with the control group.…”
Section: Discussionsupporting
confidence: 82%
“…1,2,[4][5][6][7][8][9]28,[44][45][46][47] In this study we found the effects of whole dietary rice bran intake on the mucosal immune system to be the induction of IgA (Fig. 1) and the enhancement of the innate immune response (Table 3).…”
Section: Discussionmentioning
confidence: 73%
“…The removal of the bran results in the loss of many prebiotic components and beneficial nutrients, including various polyphenols, essential fatty acids, and numerous antioxidants. [1][2][3] Dietary rice bran intake has been shown to aid in protection against gastrointestinal cancers, 1,4,5 improve lipid metabolism in diabetic rats, 6 and significantly lower cholesterol levels in humans 7,8 and hamsters. 9 Also, rice branderived prebiotics suppress inflammatory bowel disease 10,11 by decreasing ulceration and inducing beneficial effects on the intestinal mucosa through the production of antiinflammatory cytokines.…”
Section: Introduction Rmentioning
confidence: 99%
“…In humans, many studies have been reported on its potential implications as a UV-A filter in sunscreen cosmetics [14] and as a treatment for type 2 diabetes mellitus [12] and allergic reactions [37]. These data suggest that gamma-oryzanol, especially because of its antioxidant and scavenging activities, can be useful as an antioxidant and lipid peroxidation inhibitor (i.e., membrane stabilizing) during cryopreservation.…”
mentioning
confidence: 87%